Application of Forensic Accounting in Nepal - Upadhyay, Jitendra Prasad (NCC Journal, 2018)
Forensic accounting may not be a new concept in accounting. However it has become significant to all stakeholders like the government, investors and practitioners to regularity bodies. Forensic accounting is closely related to the legal process and has the potential to be involved in proceedings in the civil and criminal courts. It provides an accounting analysis to assist in legal matters forming the basis for discussion, debate and ultimately dispute resolution. This article presents status of application of forensic accounting in Nepal and recommends steps that should be taken for the enhancement of the utilization of forensic accounting as an effective tool for curtailing fraud and corruption in Nepal at different sectors NCC Journal Vol. 3, No. 1, 2018, Page: 82-89